Child care and social support modify the association between maternal depressive symptoms and early childhood behaviour problems: a US national study. Issue 4 (13th March 2006) - Lee, Li-Ching; Halpern, Carolyn T; Hertz-Picciotto, Irva; Martin, Sandra L; Suchindran, Chirayath M
Abstract : Objective: To investigate the presence and patterns of modification effects of the sex of the child, social support, and childcare on the relation between maternal depressive symptoms and child behaviour problems at two developmental stages. Design: Analyses are based on prospective longitudinal data from the study of early child care. Participants: A total of 1216 families were drawn from 10 locations across the USA. Mothers were age 18 or older at the time of the study child's birth and had completed outcome measures for at least one follow up time point (24 months, 36 months). Main outcome measures: Child internalising and externalising behaviour problems assessed at the child's age of 24 months and 36 months, as reported by the mother. Results: Results from generalised estimating equation analyses showed that the association between child externalising behaviour problems and maternal depressive symptoms varied according to the social support received by the mother (p<0.05). Overall, social support mitigated the relation, but protective effects diminished at increasing levels of depressive symptoms. Associations between child internalising behaviour problems and maternal depressive symptoms varied according to whether or not the child received care from caregivers other than the mother (p<0.05). Conclusions: Health providers who are working with mothers with depressive symptoms may want to examine social support that is available to mothers, especially if mothers are not severely depressed. Furthermore, recommendations to begin, continue, or perhaps increase provision of childcare from other caregivers can provide respite for mothers and opportunities for children to engage in protective interactions with others.